The cranial osteology of Buitreraptor gonzalezorum Makovicky, ApesteguÍa, and AgnolÍn, 2005 (Theropoda, Dromaeosauridae), from the Late Cretaceous of Patagonia, Argentina. Issue 1 (2nd January 2017) - Gianechini, Federico A.; Makovicky, Peter J.; Apesteguía, Sebastián
ABSTRACT: Buitreraptor gonzalezorum is a paravian theropod from the Late Cretaceous of Patagonia that has been recovered as an unenlagiine dromaeosaurid in several phylogenies. It was preliminarily described in a brief article, but a detailed osteology has not been published to date. Here we provide a thorough osteological description of the skull of the holotype, which preserves the maxillae, nasals, frontals, parietals, postorbitals, quadrates, and many mandibular bones, together with some in situ and isolated teeth. The isolated occipital condyle is the only element preserved from the braincase. Diagnostic cranial characters of this taxon include elongate skull; maxillary fenestra not dorsally displaced; posteriorly expanded postantral wall; quadrate with expanded lateral flange and a posterior pneumatic foramen; straight anterior border of the supratemporal fossa; nutrient foramina within a well-marked lateral groove on the dentary; and small, fluted teeth without denticles. Buitreraptor shares traits with Austroraptor cabazai, the only other unenlagiine to preserve cranial remains, although they also differ in the morphology of the maxillary fenestra and the presence/absence of interdental plates. A phylogenetic analysis was performed, recovering Buitreraptor as an unenlagiine dromaeosaurid, in agreement with previous works. The phylogenetic implications of some characters are discussed, including characters not previously considered for this taxon, such as the presence of the mylohyoid foramen. The distribution and codings of some characters are reconsidered, with an evaluation of how they influence the phylogenetic position of Buitreraptor and paravian relationships overall. SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Gianechini, F. A., P. J. Makovicky, and S. Apesteguía. 2017. The cranial osteology of Buitreraptor gonzalezorum Makovicky, Apesteguía, and Agnolín, 2005 (Theropoda, Dromaeosauridae), from the Late Cretaceous of Patagonia, Argentina. Journal of Vertebrate Paleontology. DOI: 10. 10.1080/02724634.2017.1255639.